2020
DOI: 10.1051/0004-6361/202037571
|View full text |Cite
|
Sign up to set email alerts
|

Plasma characterization at comet 67P between 2 and 4 AU from the Sun with the RPC-MIP instrument

Abstract: The plasma of comet 67P/Churyumov-Gerasimenko is analyzed based on the RPC-MIP mutual impedance probe data of the Rosetta mission. Numerical simulations of the RPC-MIP instrumental response considering two populations of electrons were fit on experimental responses acquired from January to September 2016 to extract the electron densities and temperatures. A time-tracking of the plasma parameters was performed, leading to the identification of a cold and a warm population of electrons during the period of inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 34 publications
6
34
0
Order By: Relevance
“…1. Attributing total densities in excess of 500 cm −3 to cold electrons gives relative abundances of the latter in the range 0 − 75%, roughly in line with preliminary estimates by (some) previous authors [Gilet et al, 2017;Engelhardt et al, 2018;Gilet et al, 2020;Wattieaux et al, 2020]. The electron gyro-radius is r Le ∼ 400 − 800 m (for T e ∼ 5 eV).…”
Section: Characterizing the Plasma Environmentsupporting
confidence: 86%
“…1. Attributing total densities in excess of 500 cm −3 to cold electrons gives relative abundances of the latter in the range 0 − 75%, roughly in line with preliminary estimates by (some) previous authors [Gilet et al, 2017;Engelhardt et al, 2018;Gilet et al, 2020;Wattieaux et al, 2020]. The electron gyro-radius is r Le ∼ 400 − 800 m (for T e ∼ 5 eV).…”
Section: Characterizing the Plasma Environmentsupporting
confidence: 86%
“…This is well modeled and reported in Wattieaux et al (2019), that developed a model of the mutual impedance response taking into account the effect of the spacecraft charging on the mutual impedance measurement. By fitting the in situ mutual impedance spectra to a dataset of modeled mutual impedance spectra in a two-electron temperature plasma, it has been shown that it is possible to detect the presence of cold electrons even when the double resonance is not visible on the mutual impedance spectra (Wattieaux et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…This process was repeated every 160 s. Each of the two probes obtained 295 such time series during the day. The power spectral density for each time series is computed, using Welch's method (Welch, 1967), averaging segments that are 256 samples long with an overlap of 65 % (Fig. 2a and b).…”
Section: Instrumentationmentioning
confidence: 99%